2003
DOI: 10.3928/0148-4834-20030401-07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Career Decisions: Perspectives of Nursing Students in Three Types of Programs

Abstract: The purpose of this study was to describe the effects of motivating factors and characteristics of the nursing profession on students selecting nursing as a career. Students from three types of programs in North Carolina (N = 495) were asked to complete a survey during the first month of their nursing program. Motivating factors influencing the decision to become a nurse were past experience with a loved one or self being ill and/or hospitalized, past health care work experience, and having a family member or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 9 publications
3
47
1
4
Order By: Relevance
“…The importance of prior experience in healthcare for choosing the career of nursing has been reported by other international studies (Beck ; Larsen et al. ). It is noteworthy that the prior personal healthcare experiences of some Singaporean students were seen to affect not only their career choice but also their preconception of nursing as a profession.…”
Section: Discussionmentioning
confidence: 63%
“…The importance of prior experience in healthcare for choosing the career of nursing has been reported by other international studies (Beck ; Larsen et al. ). It is noteworthy that the prior personal healthcare experiences of some Singaporean students were seen to affect not only their career choice but also their preconception of nursing as a profession.…”
Section: Discussionmentioning
confidence: 63%
“…Students also feel unsupported in terms of making career related decisions. This highlights the need for early career awareness, exposure to practice, advice and support prior to and throughout the degree to help better decision making to improve satisfaction with career choice 37-39. It would appear that designing a comprehensive career support mechanism across the degree may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…a.Top of mind awareness measures the specific perception coming first in students’ mind when thinking of particular career pathways 39…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified several influences on the decision to choose nursing as a career. These include family members and a desire to care for others [16, 31], exposure to healthcare environment through caring for a loved one, or prior hospital and/or work experience [31, 32]. However, these studies have taken a narrow focus either on students' characteristics, their decision, and influences at one particular time or on influences from the past.…”
Section: Limitations Of Previous Researchmentioning
confidence: 99%